Advances in research and current challenges in the treatment of advanced HER2-low breast cancer - Qin, Qiang (Frontiers in Cell and Developmental Biology, 2025)
Human epidermal growth factor receptor 2 (HER2)-low breast cancer is defined as breast cancer with an immunohistochemistry (IHC) score of 1+ or 2+ and in situ hybridisation (ISH)-negative. The traditional HER2 classification (negative or positive) has limitations, with only 15%–20% of the breast cancer population being positive and suitable for HER2-targeted therapy. The new clinical study, DESTINY-Breast04, shows that trastuzumab deruxtecan (T-DXd) has a significant effect on advanced HER2-low breast cancers, a classification that accounts for approximately half of the advanced breast cancer population. However, the detection methods and evaluation criteria for HER2-low breast cancer have not yet been standardised, and the toxicity and resistance mechanisms associated with T-DXd therapy are still unclear. This article focuses on these issues and describes the progress and challenges of T-DXd-related therapy in the treatment of advanced breast cancer patients with low HER2 expression.